Quantification of Head Shape and Cranioplasty Outcomes: Six-compartment Volume Method Applied to Sagittal Synostosis - William X.Z. Liaw, MD; William C.H. Parr, PhD; Tim S. Peltz, MD; Alex Varey, MD; Jeremy Hunt, MD; Mark Gianoutsos, MD; Damian D. Marucci, MD; William Walsh, PhD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Premature fusion of the sagittal (midline) suture between 2 parietal bones is the most common form of craniosynostosis. Surgical correction is mandated to improve head shape and to decrease the risk of raised intracranial pressure. This study evaluated the utility of 3-dimensional (3D) imaging to quantify the volumetric changes of surgical correction. Currently there is no standardized method used to quantify the outcomes of surgery for craniosynostosis, with the cranial index (width: length ratio) being commonly used. Methods:. A method for quantification of head shape using 3D imaging is described in which the cranium is divided up into 6 compartments and the volumes of 6 compartments are quantified and analyzed. The method is size invariant, meaning that it can be used to assess the long-term postoperative outcomes of patients through growth. The method is applied to a cohort of sagittal synostosis patients and a normal cohort, and is used to follow up a smaller group of synostotic patients 1, 2, and 3 years postoperatively. Results:. Statistical analysis of the results shows that the 6-compartment volume quantification method is more accurate in separating normal from synostotic patient head shapes than the cranial index. Conclusions:. Spring-mediated cranioplasty does not return head shape back to normal, but results in significant improvements in the first year following surgery compared with the preoperative sagittal synostosis head shape. 3D imaging can be a valuable tool in assessing the volumetric changes due to surgery and growth in craniosynstosis patients.